Financial Data and a New Generalization of the Skew-T Distribution - Obinna Damian Adubisi; Ahmed Abdulkadir; Umar Farouk Abbas; Haruna Chiroma (Covenant Journal of Physical and Life Sciences, 2021)
This work introduces a three-parameter hybrid model named the exponentiated half logistic skew-t distribution using the exponentiated half logistic generalised distributions. The hybrid model is appropriate for modelling skewed, heavy-and-long-tail datasets. The theoretical properties of the new model were investigated. Simulation studies performed to evaluate the finite sample performance of the parameter estimates using selected true parameter values showed that the estimates approached the true values as the sample size increased. The hybrid model efficacy, applicability and flexibility were demonstrated using the Nigeria inflation rate dataset, and the result indicated that the hybrid model outperformed several competing distributions.